2017
DOI: 10.12804/revistas.urosario.edu.co/apl/a.4150
|View full text |Cite
|
Sign up to set email alerts
|

Organización de la actividad escolar en un paciente pediátrico con alteración en el sistema ejecutivo

Abstract: Este artículo muestra el impacto de la intervención neuropsicológica infantil en la organización de la actividad escolar en un caso con alteración en el sistema ejecutivo. El desarrollo de este sistema cognitivo ha mostrado que al afectarse tiene implicaciones en el aprendizaje escolar. Este reporte de caso trata de una niña de 8 años con alteración en el funcionamiento ejecutivo y fallas en lectoescritura. Se aplicaron la Evaluación Neuropsicológica Infantil Breve, Evaluación Neuropsicológica Infantil ENI, Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Her social behaviour and apathy remained below average, however. Other authors (Domínguez‐García et al, 2022; Jiménez‐Jiménez & Marques, 2018; Serrano‐Juárez et al, 2018) have also found improvements in cognitive and behavioural variables after face‐to‐face and on‐line intervention programs for children with neurodevelopmental disorders and poor executive functions.…”
Section: Discussionmentioning
confidence: 94%
“…Her social behaviour and apathy remained below average, however. Other authors (Domínguez‐García et al, 2022; Jiménez‐Jiménez & Marques, 2018; Serrano‐Juárez et al, 2018) have also found improvements in cognitive and behavioural variables after face‐to‐face and on‐line intervention programs for children with neurodevelopmental disorders and poor executive functions.…”
Section: Discussionmentioning
confidence: 94%
“…Embora os instrumentos psicológicos utilizados nesta pesquisa sejam de reprodução não verbal, a aplicação é verbal e, portanto, requer que a criança consiga compreender a instrução verbal para executar exatamente aquilo que foi solicitado a ela. O ato de reproduzir desenhos é uma atividade que requer um esforço cognitivo que envolve uma gama de habilidades que são compensatórias para um melhor desempenho em diversas tarefas ao longo do desenvolvimento, sobretudo, as escolares (Fonseca, 2014;Jiménez-Jiménez & Marques, 2018). Sendo assim, a partir dessa consideração, buscou-se verificar se havia associação entre as habilidades cognitivas com o rendimento escolar nas disciplinas de língua portuguesa e matemática realizando uma análise de correlação de Pearson.…”
Section: Resultsunclassified